Outcomes of induction in trial of labor after cesarean delivery - Varshney, Anubha; Mohsin, Zehra (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: The objective of this study is to evaluate the outcomes of induction of labor in women attempting trial of labor after cesarean delivery and to compare maternal and neonatal morbidity and mortality in women who were induced to those delivering spontaneously. Methods: The prospective study was carried out in the Department of Obstetrics and Gynecology in collaboration with the Neonatal Section, Department of Pediatrics at J.N. Medical College and Hospital, AMU Aligarh. The sample included 280 women with one previous cesarean section, of whom 130 women underwent induction of labor (study group) and 150 were admitted with spontaneous onset of labor. Prostaglandin gel and intracervical Foley’s were used for cervical ripening in the study group. Indication of cesarean section, mode of delivery, maternal and neonatal outcome were studied in between groups. Results: Overall rate of vaginal delivery after cesarean section was 45.3% and 56% in both study and control group respectively. The rate of cesarean section were higher in women who were induced and having unfavorable cervix. Maternal and neonatal morbidity were not significantly higher as compared in both groups, however one case of scar rupture was found in study group. Conclusions: Induction of labor in women with previous cesarean section had higher rates of cesarean section however it does not adversely affect neonatal and maternal morbidity. Overall vaginal birth is safe and effective in women with previous cesarean section by prostaglandin gel or intracervical Foley’s. Authors cautiously suggest, induction of labor should be considered in preselected patient with strict monitoring.